Aerobic and anaerobic power characteristics of off-road cyclists - Baron, R. (Medicine & Science in Sports & Exercise, 2001)
PURPOSE: The purpose of this study was to describe the relationship between anaerobic power at different pedaling frequencies (including the optimal cadence) and aerobic power in off-road cyclists (CYC; N = 25) and sports students, who did not perform specific cycle exercise more than two times per week (CON; N = 60). METHODS: To describe the aerobic power, we measured the maximal power output (Wmax) and the power output at the fixed lactate threshold at 4 mmol.L-1 (WL4) obtained during a maximal aerobic power cycling test. To describe anaerobic power output, we measured the average power output (IsoWmean) over a range from 50 to 140 rpm by using a 10-s sprint on an isokinetic cycle ergometer. RESULTS: For the 10-s anaerobic test, CON and CYC showed a peak power output (IsoWpeak) of 13.3 +/- 1.4 and 14.9 +/- 1.1 W.kg-1, respectively. IsoWpeak corresponded to an optimal cadence of 100 +/- 9.3 rpm for CON and 100 +/- 8.7 rpm for CYC. There was a significant difference (P < 0.001) in the Wmax:IsoWpeak (Waerobic:Wanaerobic) ratio between CON (32 +/- 4.5%) and CYC (38 +/- 3.9%). Significant differences among group means were identified using an ANOVA test and a post hoc analysis. The off-road cyclists showed a significantly higher IsoWmean at all pedaling frequencies and at the optimal cadence (P < 0.01). There was a modest relationship between Wmax and IsoWpeak in both groups (CON r = 0.53; CYC r = 0.64; P < 0.01). CONCLUSION: Anaerobic power values are important components associated with cycle performance in both noncyclists and off-road cyclists. However, the results of the present study demonstrated the usefulness of the power index in the physiological evaluation of off-road cyclists, as it gives information on the proportion of aerobic to anaerobic energy contribution.